Patterns of early conversational recovery for people with traumatic brain injury and their communication partners. (16th April 2019) - Chia, An An; Power, Emma; Kenny, Belinda; Elbourn, Elise; McDonald, Skye; Tate, Robyn; MacWhinney, Brian; Turkstra, Lyn; Holland, Audrey; Togher, Leanne
ABSTRACT: Primary objective : To investigate whether the degree of participation by people with severe Traumatic Brain Injury (TBI), and the degree of support by their communication partners (CPs) changes in conversation during subacute recovery. Methods and procedures : Seventeen pairs of participants with TBI and their CPs were video-recorded during a 10 min casual conversation at 3 and 6 months post-injury. Communication behaviors were rated using the adapted Measure of Participation in Conversation (MPC) and the adapted Measure of Support in Conversation (MSC) at both time points and compared. Results : Inferential analyses showed that there was no significant change in the degree of participation in conversation by participants with TBI and the degree of conversation support by their CPs from 3 to 6 months post. Comparison of qualitative field notes revealed that specific conversational behaviors changed over time, including better turn-taking and topic maintenance. Conclusion : Documenting early communication recovery is a complex and challenging endeavor. The lack of change in conversational effectiveness during the sub-acute period using global rating scales highlights the need for social communication tools that are sensitive to communication recovery following severe TBI.